A Revenge or a Challenge to Patriarchy? a Feminism Study of Kill Bill Movie - Lisa Andriyani; Teguh Kasprabowo (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research is intended to advance a more comprehensive understanding of how gender is portrayed in movies and how this medium may be used to investigate and discuss feminist problems. Furthermore, this study may give rise to conversations concerning the significance and influence of patriarchal narratives in a broader societal setting, as well as the part that women play in opposing repressive authorities. Qualitative methods are used, screening the film "A Feminism Study of Kill Bill Movie" through theory. The steps include reading, categorizing, and analyzing the text. No numerical data is required. Conclusions and suggestions are drawn from the research findings.  Based on the analysis, it can be concluded that *Kill Bill* serves not only as a narrative of personal revenge but also as a profound feminist statement against patriarchal oppression. Beatrix Kiddo's journey reflects a multifaceted resistance against various forms of gender-based subjugation, including objectification, control over bodily autonomy, and the imposition of traditional gender roles. Through her actions—reclaiming her right to life, motherhood, personal agency, and confronting male authority figures such as Bill—the protagonist symbolizes the overthrow of patriarchal dominance and the assertion of female power and identity. The study reveals that Beatrix's revenge transcends individual retaliation, positioning her as an agent of social and ideological change who challenges the oppressive structures embodied by male characters and institutions in the film. The narrative successfully blends visual symbolism, dialogue, and character development to project a strong feminist discourse, aligning with the principles of empowerment, resistance, and self-determination advocated in feminist theory. Thus, *Kill Bill* can be interpreted as both a personal struggle and a broader feminist rebellion against the systemic forces of patriarchy.